Price and wage formation in Portugal - Carlos Robalo Marques; Fernando Martins; Pedro Portugal (European Central Bank (ECB), 2010)
This paper brings together empirical research on price and wage dynamics for the Portuguese economy based both on micro and macro data. As regards firms' pricing behaviour the most noticeable finding is that prices in Portugal are somewhat less flexible than in the United States but more flexible than in the Euro Area. Regarding firms' wage setting practices, we uncover evidence favouring the hypothesis of aggregate and disaggregate wage flexibility. Despite the existence of mandatory minimum wages, the presence of binding wage floors and the general use of extension mechanisms, the firms still retain some ability to circumvent collective agreements via the mechanism of the wage cushion. The evidence also suggests that Portuguese wages behave in a fashion consistent with the wage curve literature, but the responsiveness of real wages to unemployment changes may have declined over the last decade.
Keywords: C42; D40; E31; J30; 330; Persistence; survey data; wage and price rigidities; wage cushion; Lohnrigidität; Preisrigidität; Preismanagement; Lohnbildung; Portugal